An experimental study of the neurophysical mechanisms of photophobia induced by subarachnoid hemorrhage. (6th September 2016) - Aydin, Nazan; Kotan, Dilcan; Keles, Sadullah; Ondas, Osman; Aydin, Mehmet Dumlu; Baykal, Orhan; Gundogdu, Betul
Highlights: In our previous studies, we have reported that the parasympathetic preganglionic denervation of the CG can occur in patients with SAH or meningitis as the result of an arterial rupture in the subarachnoid space. The purpose of this study was to investigate the potential relationship between SAH-induced neuronal degeneration in the CG, pupil diameters and photophobia scores in rabbits. In our previous studies in SAH animal models, we studied the relationship between the neuronal density in the autonomic ganglia of cranial nerves and vasospasm in the cerebral arteries. This study could contribute to a better understanding of the pathways involved in SAH-induced photophobia. Abstract: Background: Photophobia is defined as a painful psychosomatic discomfort triggered by intense light flow through the pupils to the brain, but the exact mechanism through which photophobia is induced by subarachnoid hemorrhage (SAH) is not well understood. In this study, we aimed to investigate whether there was any relationship between the mydriasis induced by the degeneration of the ciliary ganglion (CG) and photophobia in instances of SAH. Materials and methods: Five of a total of 25 rabbits were used as the intact control group; five were used in the sham-operated control group; and the remaining 15 were used as the SAH group, which was created by injecting autologous blood into their cisterna magna. All animals were examined daily for 20 days to evaluate their level of photophobia, after which their brains, CGs and superior cervical ganglia (SCGs) were extracted bilaterally. The densities of normal and degenerated neurons in these ganglia were examined by stereological methods. Results: In SAH animals with a high photophobia score, the mean pupil diameter and density of degenerated neurons density in the CG were greater than in cases with a low photophobia score ( p  < 0.05). Further analysis revealed that the increase in the density of degenerated neurons in the CG following SAH resulted in the paralysis of the parasympathetic pathway of the pupillary muscles and mydriasis, which facilitates the excessive transfer of light to the brain and photophobia. Conclusion: Our findings indicate that SAH results in a high density of degenerated neurons in the CG, which induces mydriasis and is an important factor in the onset of photophobia. This phenomenon is likely due to more light energy being transferred through mydriatic pupils to the brain, resulting in vasospasm of the supplying arteries.